FIGURE 4. Paralomis makarovi n in Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution - Hall, Sally; Thatje, Sven (Zenodo, 2009)
FIGURE 4. Paralomis makarovi n. sp. a, c, e, f: male holotype, 23.8 mm CL (USNM 1122582), Bering Sea, Bowers Bank, 54°30'N, 179°17'E, 629 m. (a) carapace, dorsal. (c) dorsal carapace spines, lateral. (e) left pereiopod 4, posterior. (f) rostrum, lateral. Paralomis multispina Benedict. b, d: USNM 18592, female, 20 mm CL. (b) carapace, dorsal. (d) mid-branchial carapace ornamentation, dorsal. Scale bar = 5 mm for a, b, e; 1mm for c, d, f. Published as part of Hall, Sally & Thatje, Sven, 2009, Four new species of the family Lithodidae (Decapoda: Anomura) from the collections of the National Museum of Natural History, Smithsonian Institution, pp. 31-47 in Zootaxa 2302 on page 38, DOI: 10.5281/zenodo.191756